(untitled) (AmeriQuests, 2008)
Considerable variation exists in African American men’s involvement in family life. In-depth interviews were conducted with forty-five Black fathers of young children regarding their life histories and self-reported contribution to the division of housework. This article examines the impact of men’s job experiences and love relationships on their family involvement. Paternal involvement is both a function of structural constraints and of men’s interpretations and actions about them. Of paramount importance are how men construe their experiences on the job market and how they feel about the breadwinning ethic. In addition, women affect men’s behavior by mediating their connections with their children, either as former lovers or as current partners. For those who lived with women, their participation in housework is also related to their partners’ employment status.